2022
DOI: 10.1021/acsami.2c09194
|View full text |Cite
|
Sign up to set email alerts
|

Particle Surface Cracking Is Correlated with Gas Evolution in High-Ni Li-Ion Cathode Materials

Abstract: High-Ni layered oxide cathode materials (LiNi x TM(1–x)O2, where x > 0.8) are of great interest because they offer increased capacity compared to current commercial materials within a narrow voltage range. However, recent studies have shown that these materials in their current form suffer from capacity fading when an upper cutoff voltage above 4.3 V vs Li/Li+ is used. While many studies have focused on the H2 → H3 transition as the primary cause of capacity fading, gas evolution studies show that degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…62 The required peroxo-like intermediates have not been observed (via titration-mass spectrometry) by Kaufman et al, which instead link surface crack formation resulting from parasitic reactions with the electrolyte to gas evolution of layered Ni-rich oxide cathodes. 63 This provides further support for the assumption that larger volume variations, due to the absence of pillaring ions, lead to stronger gas evolution. Furthermore, various facets of different stability are found in LNO, and the presence of electrolyte solvent, especially EC, has also been shown to affect the activation energy for lattice oxygen release.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…62 The required peroxo-like intermediates have not been observed (via titration-mass spectrometry) by Kaufman et al, which instead link surface crack formation resulting from parasitic reactions with the electrolyte to gas evolution of layered Ni-rich oxide cathodes. 63 This provides further support for the assumption that larger volume variations, due to the absence of pillaring ions, lead to stronger gas evolution. Furthermore, various facets of different stability are found in LNO, and the presence of electrolyte solvent, especially EC, has also been shown to affect the activation energy for lattice oxygen release.…”
supporting
confidence: 52%
“…Yet, Genreith-Schriever et al suggest dimer formation from oxygen atoms of the same layer and under assistance of H 2 O, while also pointing to the predominance of the (012) facet and arguing that oxygen, not nickel, is the main redox contributor to LNO capacity . The required peroxo-like intermediates have not been observed (via titration-mass spectrometry) by Kaufman et al, which instead link surface crack formation resulting from parasitic reactions with the electrolyte to gas evolution of layered Ni-rich oxide cathodes . This provides further support for the assumption that larger volume variations, due to the absence of pillaring ions, lead to stronger gas evolution.…”
Section: Resultsmentioning
confidence: 93%
“…All three materials exhibit the representative phase transformation behaviors in Ni-rich cathodes: the hexagonal to monoclinic (H1−M) phase transformation in 3.5−3.8 V, the M−H2 phase transformation at 4.0 V, and the detrimental H2−H3 transformation at 4.2 V. 48,49 The H2−H3 transformation is regarded to be related to gas evolution issues, including oxygen release and side reactions. 50,51 Interestingly, although both Al 3+ and Ti 4+ showed a slight optimization effect on the cycling performance with the cutoff voltage 4.3 V, the H2−H3 transformation exhibited no observable difference for the undoped and doped materials. To understand the influence of doping strategy on lattice oxygen stability, coulometric titration and thermodynamic analysis were conducted for quantitative discussion.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…This may indicate that the defective initial morphology of the cathode active material is also highly detrimental to cycling stability because extensive research has revealed that defects usually initiate from surface and grain boundaries. Compared with fine particles, the uneven and defective particle increases the surface area and thus the direct exposure to electrolyte, leading to severer surface deterioration. The voltage vs state of charge curves and corresponding differential capacity curved are plotted in Figure b–g. All three materials exhibit the representative phase transformation behaviors in Ni-rich cathodes: the hexagonal to monoclinic (H1–M) phase transformation in 3.5–3.8 V, the M–H2 phase transformation at 4.0 V, and the detrimental H2–H3 transformation at 4.2 V. , The H2–H3 transformation is regarded to be related to gas evolution issues, including oxygen release and side reactions. , Interestingly, although both Al 3+ and Ti 4+ showed a slight optimization effect on the cycling performance with the cutoff voltage 4.3 V, the H2–H3 transformation exhibited no observable difference for the undoped and doped materials. To understand the influence of doping strategy on lattice oxygen stability, coulometric titration and thermodynamic analysis were conducted for quantitative discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Differential Electrochemical Mass Spectroscopy: DEMS was used to detect the gases evolved from the battery during cycling at room temperature and has been used extensively by Kaufman, McCloskey, and colleagues to quantify gas evolution from a variety of Li-ion cathode materials and metal-air batteries. [25,38,39] The DEMS setup and calibration is extensively described in the appendix of Renfrew's thesis. [40] The DEMS cell was designed to be hermetically sealed (confirmed with a helium leak check), with inlet and outlet capillaries connecting the DEMS gas handling system to the cell headspace.…”
Section: Electrochemical Measurements and In Situ X-ray Diffractionmentioning
confidence: 99%